Upaya Pemulihan Fungsi Sosial bagi Narapidana Usia Lanjut di Lembaga Pemasyarakatan Kelas IIB Karangasem - Ayu Made Diah Pramesti; Umar Anwar (UIN Fatmawati Sukarno Bengkulu, 2022)
Penitentiary is a judicial institution that functions to foster and improve convicts so that they are aware of the mistakes they have made. It also refers to the restoration of the social function of elderly prisoners, which consists of 3 things, namely: optimizing mental and spiritual programs, implementing recreational programs and providing support through pre-release programs. The purpose of this study was to determine the implementation of the restoration of the social function of the elderly inmates in the Class IIB Karangasem Penitentiary with the elderly factor experiencing physical decline and limitations in order to achieve the goal of correctional. This research was conducted by qualitative method (case study design). Data collected using literature study, interview, observation and documentation and alalyzing by interactive model. The results of the research are that the implementation of the restoration of the social function of elderly prisoners in the Class IIB Karangasem prison has not been carried out optimally that: mental and spiritual programs only utilize religious activities, recreational programs for prisoners are carried out only for entertainment, not balancing with sports, and pre-release programs that lack knowledge. elderly inmates about the program. Barriers to the implementation of the restoration of the social function of elderly prisoners such as lack of awareness, lack of interest in reading books, and lack of socialization from correctional officers in Karangasem Prison.